The Representation of Anti-Racism in ‘Us’ Movie by Jordan Peele: Semiotics Approach: Penelitian - Mutiara Indah, N. D; Wulan Mutiara (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This thesis is entitled “The Representation of Anti-Racim in ‘Us’ Movie by Jordan Peele: Semiotics Approach”. It focuses on three primary questions; (1) What are the signs of anti-racism represented in ‘Us’ movie? (2) What are the semiotic signs that are found in the movie of ‘Us’? (3) What are the denotative and connotative meanings of anti-racism in the ‘Us’ movie? This research aims to understand the meaning of signs by Barthes’s theory of semiotics. The writer used a qualitative descriptive method. The primary data source in this research was taken from the movie ‘Us’ by Jordan Peele. After the data was collected, the writer began to analyze each in pictures and text. The result found anti-racist behavior towards racial diversity represented in the ‘Us’ movie. This attitude sincerely wants to feel the thoughts and feelings of others, the same chance to get an education, the importance of equal rights, and tolerance behavior.